Right Brain Empowerment in the Learning Process within the Classroom through the Hypnotic Language Transformation Pattern - Nurtaqwa Amin (Fakultas Sastra - Universitas Muslim Indonesia, 2019)
The language approach pattern is one of the most important strategies in the process of transforming learning material in the classroom, because a learning material can be accepted and understood well and is easier for learners to rely heavily on the techniques of using spoken language in transferring knowledge. Based on this, this study uses a hypnotic language pattern approach (transformation pattern